2021
DOI: 10.1038/s41434-021-00259-5
|View full text |Cite
|
Sign up to set email alerts
|

Automated production of CCR5-negative CD4+-T cells in a GMP-compatible, clinical scale for treatment of HIV-positive patients

Abstract: Ex-vivo gene editing in T lymphocytes paves the way for novel concepts of immunotherapy. One of those strategies is directed at the protection of CD4+-T helper cells from HIV infection in HIV-positive individuals. To this end, we have developed and optimised a CCR5-targeting TALE nuclease, CCR5-Uco-hetTALEN, mediating high-efficiency knockout of C-C motif chemokine receptor 5 (CCR5), the HIV co-receptor essential during initial infection. Clinical translation of the knockout approach requires up-scaling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“… 6 In order to scale up our process, we initially focused on the identification of transfection conditions that permit high gene-transfer rates and low electroporation-associated toxicities. In accordance with prior studies reported by Alzubi et al 10 and Schwarze et al , 24 we modified pulse strength, length, mode and direction to arrive at a bi-pulse shock that permitted high frequencies of stable gene-transfer and high viability in activated CD8 and CD4 T cells. We then performed titration experiments to determine the optimal amount of MC DNA for electroporation and defined a sweet spot with maximum yield of CAR-expressing T cells.…”
Section: Discussionmentioning
confidence: 60%
“… 6 In order to scale up our process, we initially focused on the identification of transfection conditions that permit high gene-transfer rates and low electroporation-associated toxicities. In accordance with prior studies reported by Alzubi et al 10 and Schwarze et al , 24 we modified pulse strength, length, mode and direction to arrive at a bi-pulse shock that permitted high frequencies of stable gene-transfer and high viability in activated CD8 and CD4 T cells. We then performed titration experiments to determine the optimal amount of MC DNA for electroporation and defined a sweet spot with maximum yield of CAR-expressing T cells.…”
Section: Discussionmentioning
confidence: 60%
“…Immunophenotyping of cells expanded in the CliniMACS Prodigy was performed to further characterize the T cell subpopulations in the final product. In principle, engineered T cells should be long-lived to ensure protection for an extended period of time; however, the survival and self-renewal rates are heterogeneous among different T cell subpopulations ( 35 ). Naïve T cells (Tn) can be distinguished from memory T cells, which can be further subdivided into central memory (Tcm) and effector memory T cells (Tem) ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main TALEN tool developed, CCR5-Uco-hetTALEN, includes a heterodimeric Fok1-cleavage domain and almost completely reduces off-target effects, with the notable exception of the highly homologous CCR2 ( 145 ). This technology has advanced so much that it is now automated and can reliably generate the CCR5 knockdown in frequencies above 60% within primary T cells, 40% of which can be biallelic CCR5 mutations ( 146 ).…”
Section: Mechanisms Of Targeting Ccr5 To Inhibit Hiv-1 Disease Progressionmentioning
confidence: 99%